Public perception on landscape design towards property values of high rise residential development in Kuala Lumpur - Chan, Tong Mui; Abu Bakar, Shamsul; Saidon, Mohd Nazri (Faculty of Design & Architecture, Universiti Putra Malaysia, 2017)
Due to the scarcity of land and high land value, high rise residential are becoming a popular type of property development in Kuala Lumpur. The study investigates public perception on landscape design towards property values of high rise residential in Kuala Lumpur. It is typical in current developments that landscape infrastructure is a selling point and prominent feature. However it is vague as to whether this helps to increase the property value. Potential buyers may possibly place differential preference towards properties with landscape infrastructure should it provide benefits towards increasing the property value. The research addresses whether buyers place preference towards landscape infrastructure as a factor that would offer benefit towards increasing their property value. Proof is needed that the contribution of landscape design helps in increasing property value. A further research needs to be done in order to meet the demand and supply in landscape industry.